Laboratory Assessment of Cow Dung Ash Modified with Marble Powder as Filler Material in Asphalt Concrete in Terms of Marshall Stability and Flow Value - Gupta, Roshan Prasad; Khadka, Rajesh; Bajracharya, Nhuja (Journal on Transportation System and Engineering, 2025)
This research investigated the potential of using cow dung ash (CD) and waste marble powder (MP) as cost-effective fillers in asphalt concrete, comparing its performance and costs to traditional stone dust (SD) mixes. Using the Marshall Method, the study evaluated properties such as Marshall Stability, flow, and volumetric characteristics to determine whether cow dung ash modified with marble powder (CDMP) could offer advantages. Results showed that incorporating MP and CD into asphalt concrete improved its performance, with a mix of 3% MP and 6% CD (91% SD) achieving a 13.6% improvement in Marshall Stability compared to the traditional SD mix. However, higher CD content (above 7%) led to a slight decline in performance, suggesting that exceeding 7% CD may reduce effectiveness. The study also found that a 9% CDMP mix (3% MP, 6% CD, 91% SD) resulted in an optimal bitumen content of 5.29% and reduced asphalt concrete costs by approximately 6.19% compared to the traditional mix. The modified mixes met Department of Roads (DoR) standards, confirming the suitability of CDMP for asphalt concrete. These findings highlight the economic and performance advantages of using these waste materials as sustainable alternatives in asphalt concrete, offering an environmentally friendly and affordable solution. The study recommends promoting CDMP as a sustainable filler for flexible pavements and suggests further research to explore varying CDMP content, bitumen grades, and real-world applications.